The Impact of Hot Weather on the Academic Performance and Physical Health of Selected 3rd Year Nursing Students at the University of Saint Anthony, Philippines: A Case Study of Selected Third Year Nursing Students at the University of Saint Anthony, Philippines - Jane M. Tagum-Briones; Carlen Lagyap De Villa; Cyril B. Romero (The Indonesian Institute of Science and Technology Research, 2025)
This study explored the impact of hot weather on the academic performance and physical health of 3rd-year nursing students at the University of Saint Anthony. Using a descriptive quantitative method, data were collected from 82 respondents through a structured questionnaire. The majority of participants were female, aged 21–23, and experienced average classroom temperatures of 34°C and above. Findings revealed that high temperatures “often” affected students’ academic performance, while the impact on physical health occurred “sometimes.” Heat stress was linked to decreased concentration, fatigue, and lower information retention, posing a challenge to nursing students who face rigorous academic and clinical demands. The study underscores the need for institutional interventions to create a more conducive learning environment amid rising temperatures. An intervention plan was proposed to help mitigate the negative effects of heat exposure on nursing students.